Dinamika Ekonomi Digital di Indonesia: Peluang dan Tantangan bagi Perekonomian Nasional - Multazam, Muhammad; Nur Ilham, Rico (CV. Lafadz Jaya, 2024)
The digital economy in Indonesia has developed rapidly and has become one of the main drivers of the country's economic growth. With a large market potential and increasing internet penetration, the digital economy sector offers various opportunities for business development, job creation, and enhancing global competitiveness. However, this sector also faces several challenges, such as digital infrastructure gaps, low digital literacy, and data security and privacy issues. To maximize the potential of the digital economy, Indonesia needs to accelerate infrastructure development, improve digital literacy across all segments of society, and strengthen regulations related to personal data protection. The government, private sector, and society must collaborate to create an inclusive, secure, and sustainable digital economy ecosystem. This article discusses the dynamics of the digital economy in Indonesia, opportunities to be seized, and the challenges that must be addressed to drive growth in this sector. With the right approach, the digital economy can become a key pillar for Indonesia’s future economy.